Constituting 'Visual Attention': On the Mediating Role of Brain Stimulation and Brain Imaging Technologies in Neuroscientific Practice. (1st October 2020) - de Boer, Bas; te Molder, Hedwig; Verbeek, Peter-Paul
ABSTRACT: An important development within cognitive neuroscience is the use of Non-Invasive Brain Stimulation (NIBS), a technique which holds the promise of establishing causal relationships between brain processes and cognitive processes. However, NIBS does not allow researchers to observe neurophysiological processes, and must be coupled with imaging technologies such as Electroencephalography (EEG) for the visualization of neurophysiological change. Technologies such as NIBS and EEG are not neutral intermediaries between scientists and the world, but actively mediate the reality that scientists investigate. How these technologies shape the objects of neuroscientific study becomes clear when analyzing real-life conversations between neuroscientists researching visual attention. During the constitution of visual attention, neuroscientists need to manage a tension between the epistemic norms of 'causality' and 'reality', and how this tension is managed differs when different technologies are used. In the case of NIBS, the tension between reality and causality is managed in terms of the relation between experimental results obtained within the laboratory and the 'real' world outside of the laboratory. When NIBS and EEG are combined, neuroscientist orient to the norms of causality and reality in a different way: now, the reality of the causality obtained within scientific experiments needs to managed. This indicates that neuroscientists cannot straightforwardly assume the causal efficacy of the brain on human behavior. Instead, the coming into being of neuroscientific objects such as visual attention is both dependent on technological mediations and on how the tension between the norms of 'causality' and 'reality' is managed.